Weighted norm inequalities for Schrödinger operators on variable Lebesgue spaces - Cabral, Enrique Adrián (2024)
Fil: Cabral, Enrique Adrián. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.